2023
DOI: 10.1051/0004-6361/202345885
|View full text |Cite
|
Sign up to set email alerts
|

A light strange star in the remnant HESS J1731−347: Minimal consistency checks

Abstract: Context. Recently, Doroshenko and collaborators reported a very low-mass compact star, a Central Compact Object named XMMU J173203.3-344518 inside the supernova remnant HESS J1731-347. Its tiny mass is at odds with all calculations of minimum masses of neutron stars generated by iron cores, therefore (and even if not compellingly) it has been suggested to be a "strange star". In addition to the mass, the radius and surface temperature were extracted from the data, and the whole body of information should ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Another interesting aspect is that models incorporating the excluded volume effect naturally satisfy observations of the recently observed object by HESS [46]. This object is uniquely characterized by its very small mass and radius, which challenges theoretical models of objects containing hadronic matter [56]. As shown in Figure 5, models of strange quark matter agree more naturally with the observation of HESSJ1731.…”
Section: Discussionmentioning
confidence: 78%
“…Another interesting aspect is that models incorporating the excluded volume effect naturally satisfy observations of the recently observed object by HESS [46]. This object is uniquely characterized by its very small mass and radius, which challenges theoretical models of objects containing hadronic matter [56]. As shown in Figure 5, models of strange quark matter agree more naturally with the observation of HESSJ1731.…”
Section: Discussionmentioning
confidence: 78%
“…It was proposed that HESS J1731-347 could be a candidate for a strange quark star (QS) comprising all existing massradius measurements of CSs (Di Clemente et al 2022;Das & Lopes 2023;Horvath et al 2023). However, unpaired quark matter undergoes fast cooling, leading to difficulties in reproducing the surface temperature, presented by Doroshenko et al (2022).…”
Section: = -+mentioning
confidence: 99%
“…Along this line, the CFL quark stars have been studied within MIT bag models in light of the compact object in HESS J1731-347. Horvath et al (2023) showed that candidate XMMU J173203.3-344518 might fit into a strange star scenario that could also be consistent with heavier compact stars using the same quark EOS in the MIT bag model, and discussed a possible scenario where a small gap (Δ 1 MeV) in the CFL phase would explain the high surface temperature of XMMU J173203.3-344518. Oikonomou & Moustakidis (2023) indicated that the parameter space could be further confined to the additional requirement for a high maximum mass (M TOV 2.6 M e ; Abbott et al 2020) without violating the conformal bound (Fujimoto et al 2022).…”
Section: Introductionmentioning
confidence: 99%